Access to MRI for patients with cardiac pacemakers and implantable cardioverter defibrillators. Issue 1 (24th May 2021) - Pieri, Christopher; Bhuva, Anish; Moralee, Russell; Abiodun, Aderonke; Gopalan, Deepa; Roditi, Giles H; Moon, James C; Manisty, Charlotte
Abstract : Objective: To determine provision of MRI for patients with cardiac implantable electronic devices (CIEDs; pacemakers and defibrillators) in England, to understand regional variation and assess the impact of guideline changes. Methods: Retrospective data related to MRI scans performed in patients with CIED over the preceding 12 months was collected using a structured survey tool distributed to every National Health Service Trust MRI unit in England. Data were compared with similar data from 2014/2015 and with demand (estimated from local CIED implantation rates and regional population data by sustainability and transformation partnerships (STPs)). Results: Responses were received from 212 of 223 (95%) hospitals in England. 112 (53%) MRI units' scan patients with MR-conditional CIEDs (10% also scan non-MR conditional devices), compared with 46% of sites in 2014/2015. Total annual scan volume increased over fourfold between 2014 and 2019 (1090 to 4896 scans). There was widespread geographical variation, with five STPs (total population >3·5 million representing approximately 25 000 patients with CIED) with no local provision. There was no correlation between local demand (CIED implantation rates) and MRI provision (scan volume). Complication rates were extremely low with three events nationally in 12 months (0·06% CIED–MRI scans). Conclusions: Provision of MRI for patients with CIEDs in England increased over fourfold in 4 years, but an estimated 10-fold care gap remains. Almost half of hospitals and 1 in 10 STPs have no service, with no relationship between local supply and demand. Availability of MRI for patients with non-MR conditional devices, although demonstrably safe, remains limited.